The Optimization of the ARP Poisoning Attack Detection Model Using a Similar Approach Based on NetFlow Analysis - Atmojo, Yohanes Priyo; Hostiadi, Dandy Pramana; Susila, I Made Darma; Liandana, Made; Pradipta, Gede Angga; Ayu, Putu Desiana Wulaning (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 14 No 2 (2023): Vol. 14, No. 2 August 2023DO - 10.24843/LKJITI.2023.v14.i02.p05, 2023)
Information security and threats are a concern in the cyber era. Attacks can be malicious activities. One of them is known as ARP poisoning attack activity, which attacks by falsifying a computer's identity through illegal access to retrieve confidential information in a target computer. Besides, it has also caused service deadlocks in the network. Previous studies have been introduced for the ARP Attack Detection model using rule-based and mining-based. Still, they cannot show optimal detection performance and obtain high false positive results. This paper proposed a detection model for ARP poisoning attacks using a similarity measurement approach adopting cosine similarity. The goal is to obtain measurements of host activities similar to ARP poisoning attacks. The experiment results showed that the model got an accuracy of 97.25%, recall of 96.43%, and precision of 81% with a similarity threshold value of 0.488. Comparison results with previous studies showed higher detection accuracy than previous studies and some classification methods. It shows that the model can improve intrusion detection performance and facilitate network administrators to analyze ARP poisoning attacks in computer networks.